'Global cybersecurity legislation?' - factors, perspective and implications. (4th March 2020) - Ogu, Emmanuel C.; Ogu, Chiemela; Oluoha, Onyekwere U.
As at the time of this research, no globally adopted and unified legislation for cybersecurity exists that is currently operational, despite rife global clamours for such a legislative framework. This research paper synthesizes and reviews some of the key imposing factors, putting in perspective the surrounding realities that impede the successful actualisation of such a framework, using the qualitative-exploratory research methodology. Also, presenting the implications of these factors and associated realities for cyber peacekeeping and the struggle for a utopian global information society, and then proposing recommendations pertaining the feasibility and operability of a global cybersecurity legal framework.